Pkm Dukungan Kesehatan Mental Ibu Hamil Di Desa Pulau Rambai Wilayah Kerja Puskesmas Kampa - Alini, Alini; Novrika, Bri (Universitas Pahlawan Tuanku Tambusai, 2023)
Pregnant women are a vulnerable group experiencing psychological health problems, socioeconomic status and quality of marriage are the most important risk factors for interfering with the mental health of pregnant women. The health of pregnant women is also an important factor for the health of the child they contain. Therefore, it takes the cooperation of many parties in order to improve the mental health of pregnant women. To help and keep the mental health condition of pregnant women under control and stable, it is necessary to provide support. One form of support that can be given to pregnant women is social support. Based on these problems, through this science and technology program for the community, community service activities in Pulau Rambai Village, Working Area of ??the Kampa Health Center include: the use of science and technology in increasing mental health resilience and preventing mental health problems in pregnant women, providing mental health support programs for pregnant women (communication, information and education) to increase mental health resilience and prevent mental health problems in pregnant women, provide assistance for pregnant women to be able to share the burdens and complaints of pregnant women during their pregnancy and provide solutions related to mental health in pregnant women. Keywords: Pregnancy, Health, Mental